DESAIN CAMPER TRAILER UNTUK MOTOR TOURING MERK HARLEY DAVIDSON MODEL WL 750 - achmad makky; Amirul Nefo (Aliansi Desainer Produk Industri Indonesia (ADPII), 2022)
Abstract The COVID-19 pandemic is caused by a new type of Coronavirus named SARS-CoV-2, which is transmitted through droplets between humans. All humans activities that invite crowds and physical contact are prohibited by the Indonesian Government. Repeated and massive media coverage creates anxiety which is bad for health. In addition, the need to maintain and increase the body's immunity to be resistant to viruses is considered very important. To reduce anxiety, tourism activities that utilize natural therapy are needed while still implementing physical distancing recommendations. Bikers group which was originally synonymous with motorcades, large ceremonies, and entertainment in the current conditions is no longer relevant, because it can invite crowds and are at risk of contracting the virus. So independence and adequacy when touring are needed as a new way of adventure for individual bikers during this pandemic. Motorbikes are a means to channel your hobby of adventure and show your existence as bikers. The Camper Trailer is a solution for carrying camping facilities such as tents, groceries and cooking facilities on motorbikes that don't have sufficient storage space. In this research, the authors conducted a literacy study and field surveys to determine and be able to analyze the natural characteristics of Indonesia, especially West Java, so as to determine the standard construction constraints and user needs. Through the ethnographic approach, the author examines the Harley Club Bandoeng group and the influences of subcultures resulting in acculturation and reflecting habitual characteristics and new meanings that are interesting to study. The benefit of the output of this project is that during this period each individual bikers can still exist independently and go on adventures as is the characteristic of bikers. Keywords: Pandemic,bikers, camper trailer.